Pattern of Obesity Among Patients with Type 2 Diabetes at a Tertiary Healthcare Center in Northern Nigeria - Gezawa ID (Dove Medical Press, 2019)
Ibrahim D Gezawa,1 Andrew E Uloko,1 Baffa A Gwaram,1 Daiyabu A Ibrahim,1 Ejiofor T Ugwu,2 Idris Y Mohammed3 1Department of Medicine, Aminu Kano Teaching Hospital, Kano, Nigeria; 2Department of Medicine, Enugu State University of Science and Technology, Enugu, Enugu State, Nigeria; 3Department of Chemical Pathology, Aminu Kano Teaching Hospital, Kano, NigeriaCorrespondence: Ibrahim D GezawaDepartment of Medicine, Aminu Kano Teaching Hospital, Kano, Kano State 700001, NigeriaTel +234 803 22150 92Email gezawa01@yahoo.comPurpose: Type 2 diabetes poses a major global health threat both in the developed and developing countries. Factors responsible for the soaring epidemic of T2DM in the developing countries include urbanization, ageing population, physical inactivity and increasing obesity rates. Our aim was to determine the pattern of obesity among patients with T2DM at the Aminu Kano Teaching Hospital (AKTH), Kano, Northwestern Nigeria.Patients and methods: We consecutively recruited 220 patients with type 2 diabetes attending the diabetes clinic of AKTH for the study. Patients with Type 1 diabetes, patients who could not stand or are wheelchair bound and pregnant women were excluded from the study. A pretested questionnaire was used to collect data on socio-demographic characteristics, treatment history for diabetes and history of hypertension from each participant.Results: Of the 220 patients recruited for this study, 97(44.1%) were men, while 123(55.9%) were women. The prevalence of generalized obesity among the study participants was 27.4% (women −30.9% vs men- 22.7%, X2=4.76, p=0.190). Grades I. II and III obesity were found in 17.3%, 5.9% and 3.2% of the study participants, respectively. All the participants with grade III obesity were women. Central obesity defined by WC was detected in 111(50.5%) [20(20.6%) men and 91(73.9%) women, X2=1.93, p=0.001]. Obesity defined by WHR was recorded in 182(82.7%) participants [80(43.9%) men and 102(56.0%) women, X2= 1.97, 0.001]. Using a cut-off of ≥0.5, abnormal WhtR was detected in 179(81.4%) [72(40.2%) men and 107(59.8%) women, X2= 5.82, p=0.01], while using a cut-off of ≥0.6, abnormal WhtR was detected in 84(38.2%) participants [29 (34.5%) men and 55(65.5%) women, X2=6.38, p=0.09]. Hypertension was detected in 103(46.8%) participants, with a higher prevalence among women compared with men [46.3. % vs 47.4%, X2= 1.03 p=0.87].Conclusion: The prevalence of obesity in our cohort of patients with type 2 diabetes was high. The predominant form of obesity was central obesity, which was most prevalent when indexed by WHR. The WhtR was as good as the WHR, but fared better than WC in detecting central obesity in our patients.Keywords: type 2 diabetes, obesity, central obesity, prevalence, Nigerians